Advances in nano-biomaterials and their applications in biomedicine. Issue 1 (14th May 2021) - Patil-Sen, Yogita
Abstract : Nanotechnology has received considerable attention and interest over the past few decades in the field of biomedicine due to the wide range of applications it provides in disease diagnosis, drug design and delivery, biomolecules detection, tissue engineering and regenerative medicine. Ultra-small size and large surface area of nanomaterials prove to be greatly advantageous for their biomedical applications. Moreover, the physico-chemical and thus, the biological properties of nanomaterials can be manipulated depending on the application. However, stability, efficacy and toxicity of nanoparticles remain challenge for researchers working in this area. This mini-review highlights the recent advances of various types of nanoparticles in biomedicine and will be of great value to researchers in the field of materials science, chemistry, biology and medicine.